KINERJA GURU YANG TERSERTIFIKASI DALAM MENGAJAR MATA PELAJARAN PRODUKTIF DI DEPARTEMEN BANGUNAN SMK NEGERI 1 BLITAR - TATARIA dharma DHARMA ASIH (Jurnal Kajian Pendidikan Teknik Bangunan, 2013)
This research aimed to identify trends in the performance of certified teachers who teach productive subjects in the Department of Building at the 1st Blitar State Vocational School. The performance includes performance in planning, implementing, and evaluating learning, and conduct follow-up assessments of student achievement. The population of this research was conducted with 12 teachers who teach productive subjects in the Department of Building. The sampling technique that used are the technique of documentation, observation, and deployment of student questionnaire responses. The analysis technique that used is quantitative descriptive technique. The result of this result was included the perfomance trend of certified teachers in the plan of learning which includes the preparation of (1) a syllabus with high category; (2) annual program with very high category; (3) semester program with very high category; (4) lesson plans with a completeness with high category. The performance of certified teachers in implementing learning are included in the very high category. The trend of the teachers performance to evaluate learning which includes the preparation of (1) the grating LP with very low category; (2) compilation LP with high category; (3) preparation item grating with very low category; (4) preparation items with high category; (5) preparation answer key with high category; (6) preparation of a list of values ??with high category; (7) drafting guidelines mastery with high category. The trend of the performance of teachers certified in implementing the follow-up assessment with low category. The results of the questionnaire responses of students to teacher performance are includes in the high category. Keywords: The Performance of Certified Teacher; planning, implementing, and evaluating learning; conduct follow-up assessments of student achievement Abstrak Penelitian ini bertujuan untuk mengetahui kecenderungan kinerja guru yang tersertifikasi dalam mengajar mata pelajaran produktif di Departemen Bangunan SMK Negeri 1 Blitar. Kinerja guru yang dimaksud adalah kinerja dalam merencanakan, melaksanakan, dan mengevaluasi pembelajaran, serta melaksanakan tindak lanjut hasil penilaian prestasi belajar siswa. Populasi penelitian ini adalah seluruh guru mata pelajaran produktif di Departemen Bangunan yang berjumlah 12 guru. Teknik pengambilan data yang digunakan adalah teknik dokumentasi, observasi, dan penyebaran angket respon siswa. Teknik analisis yang digunakan adalah teknik deskriptif kuantitatif. Hasil dari penelitian ini didapatkan kecenderungan kinerja guru yang tersertifikasi dalam merencanakan pembelajaran yang meliputi penyusunan (1) Silabus dengan kategori tinggi, (2) Program Tahunan dengan kategori sangat tinggi, (3) Program Semester dengan kategori sangat tinggi, (4) RPP dengan kategori tinggi. Kecenderungan kinerja guru dalam melaksanakan pembelajaran dengan kategori tinggi. Kecenderungan kinerja guru dalam mengevaluasi pembelajaran yang meliputi penyusunan (1) Kisi-kisi LP dengan kategori sangat rendah, (2) Lembar Penilaian dengan kategori tinggi, (3) Kisi-kisi soal dengan kategori sangat rendah, (4) Butir soal dengan kategori tinggi, (5) Kunci Jawaban dengan kategori tinggi, (6) Daftar nilai dengan kategori tinggi, (7) Pedoman ketuntasan dengan kategori tinggi. Kecenderungan kinerja guru dalam melaksanakan tindak lanjut hasil penilaian dengan kategori rendah. Kecenderungan kinerja guru menurut angket respon siswa dengan kategori tinggi. Kata kunci: Kinerja Guru yang Tersertifikasi, Merencanakan Pembelajaran, Melak-sanakan Pembelajaran, Mengevaluasi Pembelajaran, Melaksanakan Tindak Lanjut Hasil Penilaian Prestasi Siswa